Multi-step treatment for acquired alexia and agraphia (Part I): efficacy, generalisation, and identification of beneficial treatment steps. Issue 4 (21st April 2019) - Johnson, Jeffrey P.; Ross, Katrina; Kiran, Swathi
ABSTRACT: Reading and writing impairments are common in individuals with post-stroke aphasia. Treatment typically aims to improve the function of one of these modalities by strengthening aspects of either lexical or sublexical processing. In the present study, eight adults with acquired alexia and agraphia were administered a comprehensive treatment targeting specific lexical and sublexical processes underlying reading and/or writing. Two participants were trained in reading and six were trained in writing. Throughout treatment, reading and writing accuracy were monitored for trained items, as well as untrained but orthographically and semantically related items. Linear mixed effects models indicated that the most substantial gains were made on trained items in the trained modality; generalisation to trained items in the untrained modality and untrained but related items in both modalities was also observed. Participants improved significantly on a subset of treatment steps intended to address lexical access and representations, sublexical conversion mechanisms, and the graphemic and/or phonological buffer processes in both modalities. These results demonstrate the efficacy of a novel, comprehensive treatment protocol and suggest that targeting multiple reading and writing processes in conjunction may facilitate widespread generalisation.